Helping MSMEs Use The Marketplace - Ratih Kusumastuti; Rika Riwayatiningsih; Ekbal Santoso; Syamsu Rijal; Nuridha Matiin; Azhar Ibrahim (International Journal of Community Engagement and Development, 2024)
To support the government's efforts to encourage the adoption of digital technology for MSMEs to adapt to consumer behavior in the current digital era, Community Service activities are carried out through the distribution of training and training in the market via the market education website. The aim of this activity is to increase the knowledge and skills of MSME players so that they can sell and market their goods using the current marketplace platform. This community service activity is carried out online using the Zoom application. The implementation method consists of three stages: planning, implementation, and evaluation. The socialization of marketplace training presentations to 25 MSME participants in the Bandung Regency area was carried out through the Marketplace Education website. The expected result of this socialization is that MSME players will gain better knowledge and skills through market-related training available through the market education website. The results of completing the questionnaire by twenty MSME actors involved as respondents showed that 85% of participants really needed it and 15% needed to take further training to increase their knowledge and abilities about the market. This activity increases the knowledge of MSME players about how to create marketing strategies and display products that attract consumer interest in the market.